Pengoptimalan Inventory Level dan Cost dengan Menerapkan Direct Delivery System dan Milk-run Study pada Pengiriman Barang di PT SEMB - David Setiawan; Benedictus Rahardjo (Jurnal Titra, 2021)
PT SEMB is a company that works in the production of electrical components related to energy management and automation. The problem that occurs is the order made in the present conditions is still not optimal, causing the inventory level to be high. The study was conducted to help the company to be able to reduce the inventory costs and transportation costs. Direct delivery is a system that helps to reduce the inventory level and cost to the cost of goods ordered. The simulation that has been done for direct system can provide savings of up to 50,000 USD. Savings obtained from this direct system if applied to all local suppliers will reduce the cost of 280,000 USD compared to the current conditions. In addition, milk-run studies are also used to material pick-up methods. This method can also reduce the transportation costs until 900 USD.